Role of the Government Loans in the Development of Small Enterprises "Analytical Study of Small Enterprises in Iraq" - Shatha Abdul Hussein Jabur; Anwar Mustafa Hasan (Journal of Madenat Alelem University College, 2019)
The small enterprises that have attracted the attention of most countries of the world are one of the economic sectors and because of their role in producing, operating, income generation, innovation and technological progress as well as the role of these projects in achieving economic and social goals to reduce the unemployment problem by providing jobs for individuals with relatively different skills to expand the development of the country to include all fields and provide job opportunities.  At the present time, the role of small industries is emphasized as the most effective mode of moving the labor force towards the industrialization process. The international experience has confirmed that the development of small enterprises is important in achieving economic development and eliminating unemployment by legislation enacting and laws to activate this sector. And till know the development and effective this kind of project obstruct to the achievement of comprehensive sustainable development, by reducing unemployment, increasing revenues and thus will improving the country's gross domestic product.  Encouraging small-scale entrepreneurs will help to achieve a significant boom and quality at the economic and social levels of the country. However, the big problem that facing these projects is the provision of necessary financing for their development and expansion if the owners of these projects face great difficulty in obtaining a sufficient and appropriate source of funding. The main sources of funding for these projects is the government support, which contributes to give them the legal status, as well as the establishment of funds to finance them, as was implemented in Iraq, by establishing the Small Projects Support Fund in 2012. This research aims shedding light on the role of this fund for supporting and developing small enterprises for reducing the problem of unemployment and job opportunities creation.